Tyrosine phosphorylation of LRP6 by Src and Fer inhibits Wnt/β‐catenin signalling - Chen, Qing; Ramialison, Mirana; Wittbrodt, Joachim (EMBO reports, 2014)
Low‐density lipoprotein receptor‐related proteins 5 and 6 (LRP5/6) function as transmembrane receptors to transduce Wnt signals. A key mechanism for signalling is Wnt‐induced serine/threonine phosphorylation at conserved PPPSPxS motifs in the LRP6 cytoplasmic domain, which promotes pathway activation. Conserved tyrosine residues are positioned close to all PPPSPxS motifs, which suggests they have a functional significance. Using a cell culture‐based cDNA expression screen, we identified the non‐receptor tyrosine kinases Src and Fer as novel LRP6 modifiers. Both Src and Fer associate with LRP6 and phosphorylate LRP6 directly. In contrast to the known PPPSPxS Ser/Thr kinases, tyrosine phosphorylation by Src and Fer negatively regulates LRP6‐Wnt signalling. Epistatically, they function upstream of β‐catenin to inhibit signalling and in agreement with a negative role in regulating LRP6, MEF cells lacking these kinases show enhanced Wnt signalling. Wnt3a treatment of cells enhances tyrosine phosphorylation of endogenous LRP6 and, mechanistically, Src reduces cell surface LRP6 levels and disrupts LRP6 signalosome formation. Interestingly, CK1γ inhibits Fer‐induced LRP6 phosphorylation, suggesting a mechanism whereby CK1γ acts to de‐represses inhibitory LRP6 tyrosine phosphorylation. We propose that LRP6 tyrosine phosphorylation by Src and Fer serves a negative regulatory function to prevent over‐activation of Wnt signalling at the level of the Wnt receptor, LRP6.